Absolute quantification of DNA damage response proteins - Shun Matsuda; Tsuyoshi Ikura; Tomonari Matsuda (Genes and Environment, 2023)
Abstract Background DNA damage response (DDR) and repair are vital for safeguarding genetic information and ensuring the survival and accurate transmission of genetic material. DNA damage, such as DNA double-strand breaks (DSBs), triggers a response where sensor proteins recognize DSBs. Information is transmitted to kinases, initiating a sequence resulting in the activation of the DNA damage response and recruitment of other DDR and repair proteins to the DSB site in a highly orderly sequence. Research has traditionally focused on individual protein functions and their order, with limited quantitative analysis, prompting this study’s attempt at absolute quantification of DNA damage response and repair proteins and capturing changes in protein chromatin affinity after DNA damage through biochemical fractionation methods. Results To assess the intracellular levels of proteins involved in DDR and repair, multiple proteins associated with different functions were quantified in EPC2-hTERT cells. H2AX had the highest intracellular abundance (1.93 × 106 molecules/cell). The components of the MRN complex were present at the comparable levels: 6.89 × 104 (MRE11), 2.17 × 104 (RAD50), and 2.35 × 104 (NBS1) molecules/cell. MDC1 was present at 1.27 × 104 molecules/cell. The intracellular levels of ATM and ATR kinases were relatively low: 555 and 4860 molecules/cell, respectively. The levels of cellular proteins involved in NHEJ (53BP1: 3.03 × 104; XRCC5: 2.62 × 104; XRCC6: 5.05 × 105 molecules/cell) were more than an order of magnitude higher than that involved in HR (RAD51: 2500 molecules/cell). Furthermore, we analyzed the dynamics of MDC1 and γH2AX proteins in response to DNA damage induced by the unstable agent neocarzinostatin (NCS). Using cell biochemical fractionation, cells were collected and analyzed at different time points after NCS exposure. Results showed that γH2AX in chromatin fraction peaked at 1 h post-exposure and gradually decreased, while MDC1 translocated from the isotonic to the hypertonic fraction, peaking at 1 hour as well. The study suggests increased MDC1 affinity for chromatin through binding to γH2AX induced by DNA damage. The γH2AX-bound MDC1 (in the hypertonic fraction) to γH2AX ratio at 1 h post-exposure was 1:56.4, with lower MDC1 levels which may attributed to competition with other proteins. Conclusions The approach provided quantitative insights into protein dynamics in DNA damage response.